Too Many Pan Shows? - Unknown (Trinidad Express)
The writer is of the view that poor turn-outs may force steelband aficionados and Pan Trinbago to consider, if they should re-organize the Panorama programme into fewer shows.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Panorama (Musical festival); Steel bands (Music) -- Administration -- Trinidad and Tobago